Research Book - data engineering and information security series 1 - Ibrahim, Rosziati (Penerbit UTHM, 2017)
This research book discusses the current research in Data Engineering and Information Security. It consists of 10 chapters. Chapter 1 to Chapter 5 cover the research areas under Data Engineering while Chapter 6 until Chapter 10 cover the research areas under Information Security. Data Engineering. Chapter 1 discusses the techniques used for modelling data in data engineering. Chapter 2 looks at the firefly algorithm in solving the optimization problems in data engineering. Chapter 3 proposes a new hybrid evolutionary algorithm for plant forecasting using fuzzy inference system. Chapter 4 discusses the comparative analysis for gamification approaches in education and Chapter 5 looks at performance analysis for the Swotsuite Toolkit for Web Internet of Things (IoTs). Information Security. Chapter 6 proposes an improved DDoS Detection using Hybrid N-Gram Heuristic Technique in information security area. Chapter 7 discusses the comparative analysis of Data Wiping Techniques using Android Ext4 File System. Chapter 8 looks at comparative gait analysis for criminal investigation using leave bag behind techniques while Chapter 9 discusses the comparisons of seam carving detection techniques for digital images. Finally, Chapter 10 discusses the comparative analysis for digital artifact persistence between file format for information security.